Valuation of Digital Intellectual Assets: Principles, Factors, Approaches and Methods - O. V. Loseva; I. V. Kosorukova; M. A. Fedotova; T. V. Tazikhina; N. M. Abdikeev (Финансы: теория и практика, 2022)
The object of the study is digital assets and digital intellectual assets as objects of valuation. The subject of the research are the principles, factors, approaches and methods of assessing the value of digital assets, including digital intellectual assets, in order to involve them in civil turnover in modern realities. The relevance of the problem is caused, on the one hand, by the formation of new types of assets — digital, including intellectual — in the context of digitalization of the economy and public relations, on the other — by the uncertainties arising during their identification, as well as the need to substantiate the applicability of valuation principles, approaches and methods to determine the value of such assets for further involvement in civil turnover. The purpose of the study is to substantiate the principles, factors, approaches and methods applicable to the valuation of digital intellectual assets, their approbation on specific examples (domain names). Methods of statistical and comparative analysis, generalization, classification, and valuation were used. The essential characteristics of digital intellectual assets have been defined: intangible nature, creation with the help of digital technology; manifestation of value in the information system; the ability to civil (property) turnover as objects of intellectual rights. The applicability of valuation principles, income and comparative approaches to the valuation of digital intellectual assets is substantiated. The factors influencing the value of digital intellectual assets, as well as specific factors characteristic of one of the types of digital intellectual assets — domain names are identified. An example of using the analogs method to estimate the cost of a second-level domain name in the framework of a comparative approach is shown. It is concluded that digital intellectual assets satisfying all essential characteristics can be put on the balance sheet as intangible assets, and their market value is determined on the basis of income or comparative approaches using the principles of evaluation and identified factors.